Study of rain effects on airfoils - Lee, Wei Hong. (2012)
With the increasing unpredictability of weather conditions plaguing flights, it becomes even more important to understand the ill effects of the elements that an aircraft is exposed to during air travel. Whilst the severe damage caused by hails, snow, thunderstorm and wind shear is relatively documented, the effect of general rainfall still proves to be in the infant stages of research. Since rain can potentially alter the aerodynamic profiles of an aircraft, this field of research still needs deeper analysis. This paper first goes through several research findings relating aerodynamic degeneration due to heavy rain. Next, commercial CFD tools FLUENT and GAMBIT were used to construct and simulate rain in the main analysis, by using the Discrete Phase Model (DPM) within FLUENT. The findings effectively proved a successful simulation, and degradation in aerodynamic efficiency was evident. Two intensities of rainfall were tested, and the degradation rate was found to depend on the intensity. The findings in this thesis can understandingly provide some useful information towards aviation security, while improving flight performance and efficiency. This is valuable for the operational airline industry as well as general flight safety, which is paramount in the aviation field. More research can be built on this study in this course towards improving the general safety in the aviation industry.